(untitled) (World Bulletin of Public Health, 2026)
The uncalibrated utilization of histamine H1-receptor antagonists frequently precipitates a profound disconnect between dermatological efficacy and central nervous system preservation. This study evaluates the precise pharmacokinetic parameters, neuropharmacological spillover, and clinical outcomes associated with utilizing highly lipophilic first-generation antihistamines compared to peripherally selective second-generation agents. A prospective clinical analysis was conducted involving 145 adult patients diagnosed with acute exacerbations of severe allergic dermatoses and chronic spontaneous urticaria. Subjects were stratified into two clinical pathways: a conventional therapy cohort (n=71) receiving a first-generation agent (intramuscular chloropyramine followed by oral clemastine) and a targeted modern therapy cohort (n=74) receiving a highly selective secondgeneration agent (oral levocetirizine or desloratadine). Clinical data indicate that while peripheral histamine blockade is comparable across both pharmacological classes, the structural lipophilicity of first-generation agents induces severe, often unrecognized psychomotor impairment. The conventional cohort demonstrated a 38.4% incidence of clinically significant cognitive blunting and a measured delay in objective psychomotor vigilance tasks by an average of 142 ± 18 milliseconds at peak serum concentrations. Conversely, the targeted modern cohort exhibited zero instances of severe central nervous system depression while achieving a statistically superior reduction in the Scoring Atopic Dermatitis (SCORAD) index (p = 0.022) due to enhanced receptor affinity and a prolonged elimination half-life. The dynamics of the observed results suggest that the continued reliance on first-generation antihistamines in ambulatory adults poses a severe occupational and physiological hazard. Comprehensive pharmacotherapy must actively integrate agents that lack blood-brain barrier penetrance and possess high P-glycoprotein efflux affinity to simultaneously neutralize peripheral allergic cascades and preserve cortical processing speeds